Novel Finding of Coronary Ectasia in a Case of Acute Rheumatic Fever - Thomas Weiler; Anjali Chelliah; Linda Bradley-Tiernan; E. Anne Greene (Case Reports in Pediatrics, 2013)
A 10-year-old boy presented to his pediatrician with acute fever, rash, and polyarthritis. Laboratory studies revealed elevated inflammatory markers and positive throat culture. Echocardiogram demonstrated panvalvular insufficiency consistent with acute rheumatic fever (ARF) and coronary artery ectasia. This latter finding, typically associated with Kawasaki disease, has not been previously reported in ARF.